Measuring the Governance Capacity Of The Jombang Regency Regional Government in The Implementation Of The Senior Secondary Education Policy - Nugroho Hadi Ichda Saputra; Dian Ferriswara; Ulul Albab; Sri Kamariyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe and analyze: Governance Capacity of the Jombang Regency Regional Government in the Implementation of the Upper Secondary Education Policy and Factors Inhibiting the Capacity of the Governance Capacity of the Jombang Regency Regional Government in the Implementation of the Upper Secondary Education Policy. The research is a qualitative descriptive analysis. The data analysis technique uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that there are 4 (four) factors that affect the Governance Capacity of the Jombang Regency Regional Government in the Implementation of the Upper Secondary Education Policy. First: The communication pattern carried out by the Jombang Education Office is ineffective so that the aspirations and problems that arise cannot be accommodated properly. Second: Resources & Funding, namely the implementer (policy implementer) of the resource aspect shows that Human Resources at the Jombang Regency Education and Culture Office is supported by 266 employees. Third: Implementer Attitude (Dispositions). show a positive attitude and sufficient willingness to carry out a good secondary education program. Fourth: The bureaucratic structure is quite clear, namely the Jombang Regency Education Office, the school and the Board of Education/community leaders, but the bureaucratic procedures are still long. The factors that hinder the implementation of education policies in Jombang Regency are factors that come from within are the existence of facilities and infrastructure, the motivation of teachers and students. Then the factor that comes from outside is the school's accessibility to a variety of sources, both resources and funds